Unconventional double-level structural system for under-deck cable-stayed bridges - Misiunaitė, Ieva; Daniūnas, Alfonsas; Juozapaitis, Algirdas (Journal of Civil Engineering and Management, 2012)
This paper presents a new morphology of a cable-staying system for an under-deck cable-stayed bridge. The computational method proposed in the paper has been derived for a one-strut conventional cable staying system and applied for an unconventional double-level cable-staying system. The paper describes an algorithm for the correct implementation of the interaction between the cable-staying system and the deck. The numerical examples demonstrate that the proposed computational method based on a non-linear analysis of a simply supported and additionally restrained beam-column can be used for obtaining deformation response to the considered structure. An analysis of the same problem using finite element (FE) software ANSYS was carried out to present the accuracy of the proposed method. The paper also demonstrates comparison analysis between the conventional and unconventional structural schemes for the under-deck cable-stayed bridge under symmetric and asymmetric loading.